Classical Study of Real Life Applications of Exponential Function - Shrestha, Sujeena Kumari; Thakur, Asmita; Mandal, Kripa; Purbay, Roshni; Sahani, Suresh Kumar; Sahani, Kameshwar (Al-DYAS, 2024)
One of the most prevalent applications of exponential function involves growth and decay modes. Exponential growth and decay show up in a host of applications. From population growth and continuously compounded interest to radioactive decay and Newton’s law of cooling exponential function are ubiquities in nature. In this section, we examine exponential growth and decay in the context of some of the application. In the preceding section, we examined a population growth problem in which the population grew at a fixed percentage each year. In that case, we found that the populations can be described by an exponential function. A similar analysis will show that any process in which a quality grows by a fixed percentage each year (or each day, hours, etc) can be modeled by an exponential function. Compound interest is a good example of such a process. Other applications of exponential function are bacterial growth, bacterial decay, population decline are obtained in this project (see [1-27])